Optimasi Rasio Asam Tartrat-Natrium Bikarbonat dalam Granul Effervescent Ekstrak Teh Hijau secara Granulasi Kering - AGATHA BUDI SUSIANA LESTARI; BIRGITA NATALIA DESIHAPSARI (Fakultas Farmasi Universitas Pancasila, 2011)
The aims of this research are to determine the effects of tartaric acid, sodium bicarbonate and their interaction on the physical properties of effervescent granule made by dry granulation and also to determine the optimum composition area of tartaric acid and sodium bicarbonate that produce qualified effervescent granule. The experimental study employed factorial design with two factors, i.e. tartaric acid and sodium bicarbonate, and two levels, i.e. high level and low level. The formulas were optimized on their physical properties, i.e. the granules flow rate, moisture content, disintegration time and pH of the solution. The data were statistically analyzed using Yate’s treatment with 95% level of confidence. The results show that tartaric acid was dominant in determining the disintegration time of the effervescent granules, while sodium bicarbonate was dominant in determining the moisture content of the effervescent granules. Interaction between tartaric acid and sodium bicarbonate significantly determined the flow rate of the effervescent granules and the pH of the solution. The optimum composition area of tartaric acid and sodium bicarbonate was not produced because there was one physical property of the effervescent granule that was not fulfilled, i.e. the granules moisture content.